A checklist for managed access programmes for reimbursement co‐designed by Canadian patients and caregivers. (6th April 2018) - Young, Andrea; Menon, Devidas; Street, Jackie; Al‐Hertani, Walla; Stafinski, Tania
Abstract: Introduction: Reimbursement decisions on orphan drugs carry significant uncertainty, and as the amount increases, so does the risk of making a wrong decision, where harms outweigh benefits. Consequently, patients often face limited access to orphan drugs. Managed access programmes (MAPs) are a mechanism for managing risk while enabling access to potentially beneficial drugs. Patients and their caregivers have expressed support for these programmes and see patient input as critical to successful implementation. However, they have yet to be systematically involved in their design. Objective: The aim of this study was to co‐design with patients and caregivers a tool for the development of managed access programmes. Methods: Building upon established relationships with the Canadian Organization for Rare Disorders, the project team collaborated with patients and caregivers using the principles of participatory action research. Data were collected at two workshops and analysed using a thematic network approach. Results: Patients and caregivers co‐designed a checklist comprised of six aspects of an ideal MAP relating to accountability (programme goals); governance (MAP‐specific committee oversight, patient input, international collaboration); and evidence collection (outcome measures and continuation criteria, on‐going monitoring and registries). They recognized that health‐care resources are finite and considered disease or drug eligibility criteria for deciding when to use a MAP (eg drugs treating diseases for which there are no other legitimate alternatives). Conclusions: A patient and caregiver‐designed checklist was created, which emphasized patient involvement and transparency. Further research is needed to examine the feasibility of this checklist and roles for other stakeholders.